Penerapan Aplikasi SIAPIK dalam Penyusunan Laporan Keuangan UMKM BRILink Muh. Hasib Kabupaten Bone - Ayu Pratika; Muhammad Aziz; Samsinar Samsinar (Jurnal EMT KITA, 2026)
This study aims to analyze the implementation of the Financial Information Recording Application System (SIAPIK) in the preparation of financial statements at BRILink Muh Hasib MSME in Bone Regency. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subject was the owner of BRILink Muh Hasib MSME, while the focus of the study was on the process of recording financial transactions and preparing financial statements during the period of November 1–30, 2025. Prior to the implementation of SIAPIK, the MSME's financial records were maintained manually and in a simple manner, focusing only on cash inflows and outflows without producing complete financial statements in accordance with accounting standards. This condition made it difficult for the business owner to monitor the financial position, determine business profitability, and separate personal finances from business finances. The findings indicate that the implementation of SIAPIK assists the MSME in recording transactions more systematically, efficiently, and accurately. Through this application, the MSME is able to generate financial position statements, income statements, and cash flow statements automatically in accordance with the principles of SAK-EMKM. Furthermore, the use of SIAPIK enhances the owner's understanding of the importance of structured financial management and facilitates the digital archiving of transaction records. The practical implication of this study is that SIAPIK can serve as an effective and affordable digital solution for MSMEs to improve the quality of financial reporting and support more informed business decision-making.